AKTUALISASI PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR BERBASIS AGAMA ISLAM DI KABUPATEN BANYUMAS - aldi prasetyo; Putri Sholichatin; Fildzah Mahariyah Nadilah (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Indonesia is blessed with a variety of diversity such as religion, culture, ethnicity, and language. Such differences often lead to conflicts. Islam as the majority religion, has an important role as the main axis of creating harmony. Islamic educational institutions must play an active role in seeding the value of multicultural education. The method is used descriptive qualitative. The data collection were used observation, interviews, and documentation. Its data analysis through reduction, presentation, and drawing conclusions. The results of this study explain that students at the research site are entirely uniform, The implementation of multicultural education is focused on training students to accept and appreciate differences such as skin color, hair color, learning ability, and other differences encountered in the school. The difference encountered is in the parents of students whose community organizations are different from where the children go to school. Researchers concluded that these schools have instilled the values of multicultural education, although its implementation was not yet complete. Students while attending the school are required to follow the school's values even though they have different family backgrounds. This is because every educational institution must carry out its vision and mission according to the organization of its community.